Association of Family Support, Patient Knowledge, and Drug Side Effects With Antiretroviral Therapy Adherence in HIV Patients - Sari, Rumita Ena; Herwansyah, Herwansyah; Hubaybah, Hubaybah; Putra, Andika Aldi (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2025)
Effective antiretroviral therapy (ART) is essential for controlling HIV/AIDS; however, maintaining adherence remains challenging. Patient knowledge, family support, and drug side effects are recognized as factors association adherence. In Jambi Municipality, the increasing number of HIV cases highlights the need to identify determinants of ART adherence. This study to assess ART adherence and its associated factors among HIV patients in Jambi Municipality. This cross sectional study was conducted from July to October 2024 at Raden Mattaher Public Hospital and Simpang Kawat Community Health Center. A total of 144 HIV positive adults (≥18 years) who had been on ART for at least three months were selected through multistage sampling technique. Data were collected using a validated questionnaire measuring demographics, ART knowledge, family support, and side effects. Adherence was assessed using the Morisky Medication Adherence Scale (MMAS). Chi-square tests were used to determine associations. Most participants were male (85.4%) and aged 18–50 years (84%). More than half had good knowledge (56.3%) and adequate family support (63.2%), while 71.5% reported ART-related side effects. Overall, 79.9% demonstrated poor adherence. Bivariate analysis showed significant associations between ART adherence and knowledge, family support, as well as drug side effects (p < 0.001 for all variables). ART adherence in Jambi Municipality remains suboptimal. Interventions focusing on improving patient knowledge, strengthening family involvement, and managing treatment side effects are needed to enhance adherence and health outcomes for people living with HIV.